2018
DOI: 10.1186/s13011-018-0188-8
|View full text |Cite
|
Sign up to set email alerts
|

Difference in long-term relapse rates between youths with ketamine use and those with stimulants use

Abstract: BackgroundUnderstanding the relapse risk among different illicit drugs is vital for developing an adequate relapse prevention policy. Therefore, the current study aims to explore the potential difference in long-term relapse rates between youths who use ketamine and those who use stimulants (3,4-Methylenedioxymethamphetamine [MDMA] or methamphetamine).MethodsThe study’s participants included 92 youths with ketamine use (ketamine group, mean age: 16.0 years) and 43 youths with MDMA/methamphetamine use (stimulan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…It was found that compared to patients using ketamine, those using MDMA or methamphetamine had 2.65 times higher relapse rates. This finding was consistent with our previous long-term follow-up study [36]. The difference in relapse risk was associated with the pharmacological properties of ketamine and stimulants.…”
Section: Discussionsupporting
confidence: 93%
“…It was found that compared to patients using ketamine, those using MDMA or methamphetamine had 2.65 times higher relapse rates. This finding was consistent with our previous long-term follow-up study [36]. The difference in relapse risk was associated with the pharmacological properties of ketamine and stimulants.…”
Section: Discussionsupporting
confidence: 93%
“…c People and person-years at risk: 9731 and 29 041, respectively, for males; 1920 and 5727, respectively, for females; and 11 651 and 34 768, respectively, for the total. 34.8%) and a higher rate in males (45.2%) than in females (35.5%) [45]. For comparison, the recidivism rates among the post-release prisoners who were incarcerated for using heroin or methamphetamine were higher, with a 3-year recidivism rate of approximately 65% for heroin and 58% for methamphetamine [43].…”
Section: Age (Years)mentioning
confidence: 94%
“…A Canadian outreach study of street-involved youths who used stimulants or opioids also found a 6-month relapse rate of 67% [44]. There has been only one study examining the recidivism of recreational ketamine use in a small number of adolescents who were ordered by the court to attend an outpatient family-oriented treatment program; the reported 7-year recidivism rate of 34.8% for ketamine use [45] was much lower than the 5-year recidivism rate of heroin or methamphetamine use. To date, there has been no research on recidivism among adult ketamine users anywhere in the world.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, its easy accessibility, low price, and relatively short-acting effect have led to an increase in its illegal use by teenagers as a recreational drug. It is categorized as a schedule 3 controlled drug in Taiwan and has emerged as the most common illegal drug 1 . In 2007, Shahani et al reported a new clinical entity of ulcerative cystitis related to chronic ketamine use 2 .…”
Section: Introductionmentioning
confidence: 99%